Pelatihan Pembelajaran Rancang Bangun Aplikasi Metode Segmentasi Dengan Thresholding - Rosnelly, Rika; Wahyuni, Linda; Hardianto, Hardianto; Akbar, Muhammad Barkah; Daifiria; Subhan, Zhafira Nur (LPPM Universitas Potensi Utama, 2024)
Image processing technology has attracted human attention to be studied so that it has become a science that can be accepted and understood in everyday life. An image is a representation, likeness, or imitation of an object. The output of a data recording system can be a photo, an optical signal such as a photo, an analog signal such as an image on a TV monitor, or a digital signal that can be stored directly on storage media. One of the processes in image processing (image preprocessing). One image segmentation technique is thresholding, which uses differences in brightness or darkness to distinguish objects from the background. Thresholding is based on groupings in the histogram according to certain backgrounds or objects that can be extracted by separating the groups of the histogram. Otsu thresholding is used in a variety of applications ranging from medical imaging to low-level computer vision. The Otsu method takes an approach, namely discriminant analysis, namely determining a variable that can divide foreground and background objects. This training provides excellent benefits for students in understanding objects for applying thresholding segmentation.